Information needs in cancer patients across the disease trajectory. A prospective study. Issue 1 (January 2020) - Goerling, Ute; Faller, Hermann; Hornemann, Beate; Hönig, Klaus; Bergelt, Corinna; Maatouk, Imad; Stein, Barbara; Teufel, Martin; Erim, Yesim; Geiser, Franziska; Niecke, Alexander; Senf, Bianca; et al.
Highlights: Information needs in cancer patients are high. Most of the patients reported unmet needs. Satisfaction with information did not change over the time. Anxiety and satisfaction with information are associated. Providing information for cancer patients is very important. Abstract: Objective: As satisfaction with information received is an important precondition of adherence to treatment in cancer patients, we aimed to examine the level of perceived information, information satisfaction and information needs, and examine the prospective association between information satisfaction and anxiety. Methods: In a multicenter study in Germany, 1398 cancer patients were evaluated in terms of this at baseline, after 6 and 12 months. Results: At baseline, the majority of patients reported to feel well-informed. Nevertheless, a considerable proportion reported to wish more information. The proportion of patients reporting unmet information needs declined over time (p < 0.001). Anxiety at baseline is negatively associated with information satisfaction after 6 months (β = −0.10, p < 0.01). Conversely, information satisfaction at baseline is negatively associated with anxiety after 6 months (β = −0.10, p < 0.01). At 12 months, only the negative path leading from anxiety to information satisfaction was significant (β = −0.12, p < 0.01). Conclusion: We found high levels of information received and high information satisfaction. Nevertheless, there was a considerable quantity of unmet information needs. A bidirectional relationship between information satisfaction and anxiety symptoms emerged after 6 months. Practice implications: These results underline the priority of providing information and emotional support to cancer patients to improve satisfaction with information.